Triggering of TLR‐3, ‐4, NOD2, and DC‐SIGN reduces viral replication and increases T‐cell activation capacity of HIV‐infected human dendritic cells. Issue 5 (13th April 2017) - Cardinaud, Sylvain; Urrutia, Alejandra; Rouers, Angeline; Coulon, Pierre‐Grégoire; Kervevan, Jérome; Richetta, Clémence; Bet, Anne; Maze, Emmanuel A.; Larsen, Martin; Iglesias, Maria‐Candela; Appay, Victor; Graff‐Dubois, Stéphanie; et al.
Abstract : Innate immune sensors influence DC biology and affect their susceptibility to HIV infection. While triggering by a limited set of PRR‐agonists reduces HIV replication in DC, the capacity of infected DCs to stimulate HIV‐specific CTLs is then enhanced. The TLR‐induced expression of APOBEC3G/F(A3G/F) may bridge intrinsic and adaptive immune functions of DCs. Abstract : A variety of signals influence the capacity of dendritic cells (DCs) to mount potent antiviral cytotoxic T‐cell (CTL) responses. In particular, innate immune sensing by pathogen recognition receptors, such as TLR and C‐type lectines, influences DC biology and affects their susceptibility to HIV infection. Yet, whether the combined effects of PPRs triggering and HIV infection influence HIV‐specific (HS) CTL responses remain enigmatic. Here, we dissect the impact of innate immune sensing by pathogen recognition receptors on DC maturation, HIV infection, and on the quality of HS CTL activation. Remarkably, ligand‐driven triggering of TLR‐3, ‐4, NOD2, and DC‐SIGN, despite reducing viral replication, markedly increased the capacity of infected DCs to stimulate HS CTLs. This was exemplified by the diversity and the quantity of cytokines produced by HS CTLs primed by these DCs. Infecting DCs with viruses harboring members of the APOBEC family of antiviral factors enhanced the antigen‐presenting skills of infected DCs. Our results highlight the tight interplay between innate and adaptive immunity and may help develop innovative immunotherapies against viral infections.